Expanding health insurance for the elderly of the Philippines. (12th December 2021) - Abrigo, Michael R.M.; Halliday, Timothy J.; Molina, Teresa
Summary: This paper evaluates a Filipino policy that expanded health insurance coverage of its senior citizens, aged 60 and older, in 2014. We employ an instrumental variables estimator in which the first stage is a difference‐in‐differences specification that exploits the age discontinuity at age 60, along with data from before and after the policy. First stage results show the expansion increased insurance coverage by approximately 16 percentage points. The compliers, those induced by the policy to obtain insurance, were disproportionately female and largely from the middle of the socioeconomic distribution. Second stage regressions indicate that out‐of‐pocket medical expenditures more than doubled among the compliers. We argue that this is most likely driven by an outward shift in the medical demand curve.